Crucial Role of Microbiota in Experimental Psoriasis Revealed by a Gnotobiotic Mouse Model - Stehlikova, Zuzana; Kostovcikova, Klara; Kverka, Miloslav; Rossmann, Pavel; Dvorak, Jiri; Novosadova, Iva; Kostovcik, Martin; Coufal, Stepan; Srutkova, Dagmar; Prochazkova, Petra; Hudcovic, Tomas; Kozakova, Hana; et al. (Frontiers in Microbiology, 2019)
Psoriatic patients have altered microbiota, both in the intestine and on the skin. It is not clear, however, whether this is a cause or consequence of the disease. In this study using an experimental mouse model of psoriasis induced by imiquimod, we show that oral treatment with a broad spectrum of antibiotics (ATB) or metronidazole (MET) alone mitigates the severity of skin inflammation through downregulation of Th17 immune response in conventional mice. Since some antibiotics, including MET, can influence immune system reactivity, we also evaluated the effect of ATB in the same model under germ-free conditions. Germ-free mice treated with MET did not show milder signs of imiquimod-induced skin inflammation, which support the conclusion that the therapeutic effect is mediated by changes in microbiota composition. Moreover, compared to controls, mice treated with ATB had a significantly higher abundance of the genus Lactobacillus in the intestine and on the skin. Mice treated with MET had a significantly higher abundance of the genera Bifidobacterium and Enteroccocus both on the skin and in the intestine, and of Parabacteroides distasonis in the intestine. Additionally, germ-free mice and mice monocolonized with either Lactobacillus plantarum or segmented filamentous bacteria were more resistant to imiquimod-induced skin inflammation than conventional mice. Interestingly, compared to germ-free mice, imiquimod induced a higher degree of systemic Th17 activation in mice monocolonized with segmented filamentous bacteria but not with Lactobacillus plantarum.The present findings provide evidence that intestinal and skin microbiota directly regulates imiquimod-induced skin inflammation, and emphasize the importance of microbiota in the pathogenesis of psoriasis.